Implementing shortest path calculation for 3D navigation system - Ujang, Muhamad Uznir (Penerbit UTM, 2008)
Shortest path analysis is one of a significant tool in GIS. Several algorithms can be used to utilize the analysis. Dijkstra’s algorithm has proven its capability in providing two-dimensional (2D) shortest route information. However, there are few attempts to fit the algorithm for three-dimensional (3D) shortest routes. This chapter describes the investigation and implements the algorithm for 3D environment like 3D building for indoor situations. The developed navigation system used a 3D navigational game engine. The approach works and could be extended for application including emergency and rescue operations, building management, facility management and other 3D geo-information situations.